THE CORRELATION BETWEEN STUDENTS' MOTIVATION TOWARDS STUDENTS' SPEAKING ABILITY - Amalya, Nadina Shofaa; Ma’rifatulloh, Sayid (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Speaking is a daily activity that must be done but sometimes people take it for granted. In university level, as the semester gets higher, the difficulty of learning these skills also increases. Speaking skills lectures have been taught periodically and scheduled, but the circumstances in the classroom show that the students appear to be less participatory in speaking. Based on observations and brief conversation with some students, it can be concluded that students actually like speaking lectures but students are often afraid to point out mistakes in speaking due to lack of confident, willpower, and motivation. While motivation is an important component that cannot be separated in the teaching and learning process, especially in foreign language learning. The researcher use quantitative method. The aim of this research is to find out whether there is a positive and significant correlation between students' motivation towards students' speaking ability. The correlation index between X variable and Y variable is 0.348. It means that it has weak correlation. From the calculation of both variable above and indicated to the table of interpretation of rxy above, itsinterpretation that in both of variables has correlation. It meansthat both of variables have positive correlation (one wayscorrelation). Keywords: Correlation, Motivation Speaking